Optimization of Extraction Method for Recovery of Antioxidant Phenolics from Loranthaceae Mistletoes - Parmar, R.R.; Bhuva, H.A.; Joshi, A.A.; Jadhav, R.B. (Asian Journal of Chemistry, 2010)
Effect of solvent composition on recovery of polyphenolics from Loranthaceae mistletoes and their antioxidant activities were examined in this work. All extracts contain higher amount of flavonoid content than proanthocyanidin content which is reflected by their higher antioxidant potential. On the basis of optimization of extraction method, the 70 % methanol extract of D. trigona contains higher amount of polyphenolics and flavonoids which shows IC50 values of 7.82 μg/mL in DPPH and 8.7 μg/mL in nitric oxide scavenging activity. Thus, it can become an important natural source of antioxidant phenolics.